2018
DOI: 10.1049/iet-pel.2018.5583
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of drain current saturation behaviour in GaN polarisation super junction HFETs

Abstract: The magnitude of saturation current in a power device significantly impacts its short circuit capability. In conjunction with the unprecedented miniaturisation that GaN offers, there is a compelling rationale to examine this critical parameter in GaN transistors for thermally stable and reliable power converter applications. This article presents a comprehensive analysis of the physical behaviour that yields intrinsically low drain current saturation in GaN Polarisation Super Junction (PSJ) HFETs. The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The models employed in this simulation were based on the previously reported PSJ simulation model in ref. [27]. The similar surface charges in defects are based on the research work of refs.…”
Section: Resultsmentioning
confidence: 99%
“…The models employed in this simulation were based on the previously reported PSJ simulation model in ref. [27]. The similar surface charges in defects are based on the research work of refs.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed protection circuit is implemented in a single‐phase (1‐Φ) half‐bridge as depicted in Figure 2, which is part of the low side switches of a three‐phase (3‐Φ) buck‐boost inverter for industrial motor drives as shown in Figure 3 [21]. The GaN‐based bidirectional module is constructed by two discrete GaN HEMT in source‐to‐source connection as Sa,1 and Sa,2 or Sb,1 and Sb,2 in Figure 3.…”
Section: Protection Scheme For Normally‐on Wbg Devicesmentioning
confidence: 99%
“…Furthermore, GaN devices can exhibit the bidirectional current flow capability. In this work, both the desaturation and negative power supply protection circuits are applied to a 1.2 kV polarisation super‐junction (PSJ) GaN FET [20, 21]. Since 1.2 kV PSJ GaN FETs have a limited current rating of 8A, a 650 V/85 A SiC JFET (UJ3N065025K3S) is used to validate the desaturation protection scheme for the higher current operation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the lateral structure of GaN HEMTs is susceptible to field crowding near gate terminals that prevents them supporting high breakdown voltages. 22,23) To manage the electric field, several field plates are generally used to alleviate the field stress and achieve high-voltage devices. [22][23][24][25][26] However, the use of field plates adds additional processing steps and increases manufacturing costs and area.…”
Section: Introductionmentioning
confidence: 99%
“…22,23) To manage the electric field, several field plates are generally used to alleviate the field stress and achieve high-voltage devices. [22][23][24][25][26] However, the use of field plates adds additional processing steps and increases manufacturing costs and area. 3) The use of a low-cost Si substrate for higher-voltage devices requires thicker buffer and transition layers due to lattice mismatch 27) and vertical breakdown.…”
Section: Introductionmentioning
confidence: 99%